Dry Sliding Wear Behavior of Cor-Ten Steel with Different Metallic and Ceramic Counter Bodies - Bilal Kurşuncu; Mustafa Sabri Gök; Sabri Alkan (Tribology Online)
This study investigated the dry sliding wear behavior of Cor-Ten steel, a material commonly used in harsh environments such as ports, sea bridges, and drilling rigs. Understanding how Cor-Ten steel performs in abrasive conditions is crucial for predicting potential wear issues. To assess its wear performance, tests were conducted using three types of abrasive balls: AISI-52100 steel, WC-Co, and Alumina. The wear tests involved a reciprocating ball-on-disc device at loads of 3, 7, and 10 N and sliding speeds of 0.4 mm/s and 0.8 mm/s. Results showed that the largest wear volumes occurred with the Alumina ball, while the AISI 52100 steel ball, despite its lower hardness, produced higher wear volumes than the WC-Co ball. Additionally, increased sliding speed led to higher wear volumes across all tests. SEM images revealed distinct wear tracks on both surfaces. These results provide valuable insights into the wear mechanisms of Cor-Ten steel, which can aid in optimizing material selection and maintenance strategies in marine construction.